Análise do processo de gerenciamento de resíduos de serviços de saúde do centro cirúrgico de um hospital-escola - Lima, Viviane Inada de Oliveira (2017)
The study evaluated aspects related to the management of Health Services Waste (HSW) generated within the Surgical Center (SC) of a school hospital in the interior of São Paulo, with the purpose of proposing improvements in this process. This is a qualitative quantitative study that was performed through process observation, data collection, semi-structured interviews applied to the nursing team's collaborators and the quantification of HSW generated in the Operating Room (OR). Data collection was performed in 1 week, a total of 42 interviewees, most of them (34, 80.95%) nursing technicians. As to the knowledge, 92.90% reported knowing what was HSW and 7.10% said they did not know what it was. About the Management Plan of Healthcare Waste, 54.8% were unaware and 45.20% knew. In the issue of training on HSW, 69% said they had not, 31% said yes. However, 11.90% said that it was enough and 88.10% was insufficient. Regarding segregation, 95.20% said they did not perform, and 4.80% said yes. The hamper review is performed by 100% of the employees. Of the 42 interviewees, 10 of them reported having suffered an accident at work with some kind of HSW. It was observed that there is no segregation of type B (chemical) and D (common) residues within the OR, and the medical and nursing staff do not perform the correct segregation of HSW. It was observed that the availability of the dumps inside the SC is incorrect, generating confusion in the discards of HSW. The purge ergonomics of the SC is not adequate with the needs of the employees. The HSW of 53 surgical procedures were weighed, totaling 170,157 kg, of which 116.17 kg (68.28%) infective wastes and 53,978 kg (31.72%) were common wastes. It is concluded that, even with the requirements of the RDC laws no. 306/04 of ANVISA and Res. Nº 358/05 of CONAMA that regulate the management of HSW, it was verified the possibilities of improvement so that the sector of the SC Stay in full compliance with federal law. Although there was no segregation of the HSW within the room, the collaborators proposed to segregate and were aware of its importance and the need for more lectures / orientations on the subject, that is, the need for a permanent education